La competencia intercultural como llave para el desarrollo del Perú - Gómez-Schlaikier, Sigrid (Universidad ESAN. ESAN Ediciones, 2009)
The term «intercultural competence» originally referred to the conscious skills and attitudes that the student and everyone involved in teaching a foreign language had to develop to understand the sociocultural context and decode messages from the language they were teaching-learning, meaning is no longer exclusive to this area. This article is about how the implemen-tation of intercultural competence has become very important in international relations, international cooperation, education and business; it allows optimizing the communication between different countries and cultures. Also, focus on its application to the national situation. Finally, gives an example of what can be a good practice of «intercultural competence» with the Chinese culture as a reference.

El término «competencia intercultural» originalmente se refería a las destrezas y las actitudes conscientes que el estudiante y todos los implicados en la enseñanza de una lengua extranjera tenían que desarrollar para conocer el contexto sociocultural y decodificar los mensajes del idioma que estaban enseñando-aprendiendo, acepción que ha dejado de ser exclusiva de esta esfera. Este artículo trata de cómo la aplicación de la competencia intercultural ha adquirido gran importancia en las relaciones internacionales, la cooperación internacional, los programas educativos y los negocios, pues permite optimizar la comunicación entre distintos países y culturas. Además, reflexiona acerca de su aplicación a la realidad nacional. Finalmente y como referencia, presenta un ejemplo de lo que puede ser una buena práctica de «competencia intercultural» con la cultura china.
Keywords: Globalization; Migration; Globalización; Intercultural competence; Migración; Decentralization; Competencia intercultural; Descentralización; China; China; https://purl.org/pe-repo/ocde/ford#5.02.04